Kreativitas Guru PAI dalam Penggunaan Media Handphone Pada Mata Pelajaran Pendidikan Agama Islam dan Budi Pekerti di SMP Negeri 1 Jatilawang - Astuti, Dwi; Pandini Gunawan, Yosi Intan (Sekolah Tinggi Agama Islam (STAI) AL-IKHLAS DAIRI SIDIKALANG, 2025)
This research is focused on illustrating how Islamic Religious Education instructors creatively implement mobile phone technology as a tool to aid learning in Islamic Religious Education (PAI) and Character Building at SMP Negeri 1 Jatilawang. The approach taken in this study is descriptive qualitative, utilizing methods such as observation, interviews, and documentation for data gathering. The analysis of the data includes steps like data reduction, presentation, and drawing conclusions or verifying findings. Participants in the research included the school principal, teachers of Islamic Religious Education, and students from grades VII and VIII at SMP Negeri 1 Jatilawang. To ensure the validity of the data, triangulation was employed. Findings indicated that the teachers of Islamic Religious Education displayed significant creativity in using various mobile applications including YouTube, Google Maps, Canva, Google Forms, and Islamic educational apps like the Stories of the 25 Prophets and Apostles. The digital tools were effectively integrated during the planning, execution, and assessment phases of the educational process. Some challenges encountered, such as limited devices, internet connectivity, and the need for student supervision, can be addressed through proper management techniques. In general, the incorporation of mobile phones enhances the effectiveness, involvement, and motivation of students in the Islamic Religious Education classroom.